2008
DOI: 10.1007/s11055-008-9088-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of axonopathy in the mechanisms of development of demyelination processes in the central and peripheral nervous system

Abstract: The role of axonopathy in the development of demyelinating processes in the CNS and peripheral nervous system was addressed in studies of 43 patients with multiple sclerosis (MS) and 144 patients with chronic inflammatory demyelinating polyneuropathy (CIDPN). Patients with MS were found to have foci of reduced MRI intensity in the T1 regime ("black holes," present in 28%) and regional atrophy of the cerebral cortex (in 46%), which showed a significant association with the degree of invalidity on the EDSS (Kend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Polyneuropathies (PNP) are a large group of the peripheral neuro system diseases, characterized by symmetrical diffuse lesions of peripheral nerve fibers [ 39 , 40 , 41 ]. The unit of damage in PNP is not individual nerves, but fibers that make up various peripheral nerves, the probability of damage to which depends on their length, caliber, antigenic composition, metabolic rate, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyneuropathies (PNP) are a large group of the peripheral neuro system diseases, characterized by symmetrical diffuse lesions of peripheral nerve fibers [ 39 , 40 , 41 ]. The unit of damage in PNP is not individual nerves, but fibers that make up various peripheral nerves, the probability of damage to which depends on their length, caliber, antigenic composition, metabolic rate, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated that oxidative stress and local NO levels play an important role in the initiation and progression of IVDD [19,33,37,38] and back pain [8,11]. Polyneuropathies (PNP) are a large group of the peripheral neuro system diseases, characterized by symmetrical diffuse lesions of peripheral nerve fibers [39][40][41]. The unit of damage in PNP is not individual nerves, but fibers that make up various peripheral nerves, the probability of damage to which depends on their length, caliber, antigenic composition, metabolic rate, etc.…”
Section: Prospects For the Use Of Nos Inhibitors To Modulate The Effect Of Drugs Used To Treat Back Painmentioning
confidence: 99%